Biosensors: A Protein‐Nanocellulose Paper for Sensing Copper Ions at the Nano‐ to Micromolar Level (Adv. Funct. Mater. 4/2017). (January 2017) - Weishaupt, Ramon; Siqueira, Gilberto; Schubert, Mark; Kämpf, Michael M.; Zimmermann, Tanja; Maniura‐Weber, Katharina; Faccio, Greta
Abstract : A novel biosensor 'CySense' for the nanomolar sensitive detection of heavy metal ions in complex aqueous solutions and biological samples is presented by G. Faccio and co‐workers in article 1604291. CySense films were produced by precipitation of a nanocellulose suspension previously decorated with the red fluorescent protein C‐phycocyanin. The processing into films enhanced the protein stability and enabled reuse for several cycles.